Evidence for effective interventions to reduce mental health-related stigma and discrimination in the medium and long term: Systematic review. (November 2015) - Mehta, N.; Clement, S.; Marcus, E.; Stona, A.-C.; Bezborodovs, N.; Evans-Lacko, S.; Palacios, J.; Docherty, M.; Barley, E.; Rose, D.; Koschorke, M.; Shidhaye, R.; et al.
Abstract : Background: Most research on interventions to counter stigma and discrimination has focused on short-term outcomes and has been conducted in high-income settings. Aims: To synthesise what is known globally about effective interventions to reduce mental illness-based stigma and discrimination, in relation first to effectiveness in the medium and long term (minimum 4 weeks), and second to interventions in low- and middle-income countries (LMICs). Method: We searched six databases from 1980 to 2013 and conducted a multi-language Google search for quantitative studies addressing the research questions. Effect sizes were calculated from eligible studies where possible, and narrative syntheses conducted. Subgroup analysis compared interventions with and without social contact. Results: Eighty studies ( n = 422 653) were included in the review. For studies with medium or long-term follow-up (72, of which 21 had calculable effect sizes) median standardised mean differences were 0.54 for knowledge and −0.26 for stigmatising attitudes. Those containing social contact (direct or indirect) were not more effective than those without. The 11 LMIC studies were all from middle-income countries. Effect sizes were rarely calculable for behavioural outcomes or in LMIC studies. Conclusions: There is modest evidence for the effectiveness of anti-stigma interventions beyond 4 weeks follow-up in terms of increasing knowledge and reducing stigmatising attitudes. Evidence does not support the view that social contact is the more effective type of intervention for improving attitudes in the medium to long term. Methodologically strong research is needed on which to base decisions on investment in stigma-reducing interventions.